Effect of high-intensity interval training with varying work-to-rest ratios on specific physical fitness in adolescent Taekwondo athletes - Xu, N.; Xue, Y.; Zhang, M. (European Journal of Sport Science, 2025)
This study investigated the effects of high-intensity interval training (HIIT) with different work-to-rest ratios during the same training duration on the specific physical fitness of Chinese adolescent taekwondo athletes (N = 30, 16-20 years, 18 males and 12 females, and provincial champion/runner-up or national top 6). Athletes were randomly allocated to HIIT-20S (20 s work: 10 s rest), HIIT-30S (30 s work: 10 s rest), and a control group (2 min actual combat competitive: 1 min rest). An 8-week intervention (24 sessions, 30 min/session). Specific physical fitness was assessed using the progressive specific taekwondo test, frequency speed of kick test, 10-s high roundhouse kick test, 60-s double chop kick test, heart rate recovery (HRR), 1 repetition maximum (1-RM) squat test, and improved Illinois agility test. Statistical significance was defined as p < 0.05. Compared with the HIIT-20S (1.96%) and control (0.47%) groups, the HIIT-30S group demonstrated a significantly greater improvement in VO2peak (4.72%). In the FSKT10S test, the HIIT-20S group performed better than the HIIT-30S group (2.24% vs. 1.34%), whereas the HIIT-30S group showed higher gains in FSKTtotal (5.09% vs. 2%) and a steeper decline in KDI (-21.7% vs. -12.1%). Similarly, the HIIT-20S group outperformed the HIIT-30S group in the 10S-HRK test (3.62% vs. 0.91%), whereas the HIIT-30S group outperformed the 60S-DCK test (3.45% vs. 1.91%). Improvements in agility favored the HIIT-20S group (-8.26% vs. HIIT-30S: -4.01%; control: -0.85%). Both HIIT groups showed enhanced heart rate recovery (HIIT-30S, 2.74% and HIIT-20S, 2.57%), although no significant differences were observed in lower limb maximal strength. These findings confirm the specificity of the work-to-rest ratio: HIIT-30S effectively enhances cardiorespiratory endurance and repeated kicking endurance, whereas HIIT-20S appears to be more beneficial for optimizing explosive strength, agility, kick speed, and frequency.